2021
DOI: 10.3390/ijms22094869
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Beta-Glucans Synergically Stimulate Human Macrophage Activity

Abstract: Vitamin D and beta-glucans are both immunostimulants. Vitamin D exerts its beneficial effects on many components of the immune system. In macrophages, the hormone modulates both phagocytic activity and cytokine production; therefore, it plays an important role in mediating the innate immune response to infection. The immunomodulatory properties of beta-glucans are attributed to the ability of these fungal cell wall polysaccharides to bind to different receptors expressed on the cell surface of phagocytic and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Moreover, it reduces the production of pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α), INF-γ, interleukin (IL)-6, and IL-1, while increasing anti-inflammatory cytokines such as IL-10 [ 30 , 31 , 32 ]. In particular, a recent study focused on the synergic effect of calcitriol and beta-glucans, another well-known immunomodulator, on macrophage phagocytic activity and cytokines production; the authors concluded that both molecules converge on the same pathway and that the enhanced production of immunomodulatory cytokines observed after cotreatment with the two molecules was mediated by the increased vesicular acidification [ 33 ].…”
Section: Vitamin D As Immunomodulator and Immunostimulant Against Res...mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, it reduces the production of pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α), INF-γ, interleukin (IL)-6, and IL-1, while increasing anti-inflammatory cytokines such as IL-10 [ 30 , 31 , 32 ]. In particular, a recent study focused on the synergic effect of calcitriol and beta-glucans, another well-known immunomodulator, on macrophage phagocytic activity and cytokines production; the authors concluded that both molecules converge on the same pathway and that the enhanced production of immunomodulatory cytokines observed after cotreatment with the two molecules was mediated by the increased vesicular acidification [ 33 ].…”
Section: Vitamin D As Immunomodulator and Immunostimulant Against Res...mentioning
confidence: 99%
“…On the one hand, the NF-kB signaling pathway is partially blocked by active vitamin D [ 172 , 173 , 174 ]. On the other hand, ROS generated by the NF-kB signaling pathway are neutralized by the vitamin-D-dependent increased glutathione biosynthesis [ 33 , 175 ] and by the enhanced activity of various ROS-scavenging enzymes controlled by active vitamin D [ 163 ].…”
Section: The Biochemical Basis Of the Antioxidant And Metabolic Activ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Prebiotics can furthermore aid the host's immune system in several ways: directly through immune cell stimulation (by β-glucans) or indirectly through the production of SCFA, which contributes to an increased activity of immune cells (T-helper cells, killer cells, and macrophages) [18][19][20]. Another indirect benefit is associated with competition between potentially pathogenic strains invading the gastrointestinal tract and beneficial species of bacteria (i.e., probiotics) [21].…”
Section: Prebioticsmentioning
confidence: 99%